PENDAPATAN PEMBUDIDAYA IKAN ANGGOTA KELOMPOK WIRAUSAHA PEMUDA DAN IMPLIKASINYA TERHADAP KETAHANAN EKONOMI KELUARGA (Studi Di Kelompok Wirausaha Pemuda Kota Palangka Raya, Provinsi Kalimantan Tengah) - Oktavianti, Fanny Kartika (Jurnal Ketahanan Nasional, 2014)
The group of Wirausaha Pemuda was one of programs of Kementerian Pemuda and Olahraga to grew soul of enterpreneurship at young man and assisted alleviation unemployment. Factors which affected magnitude of Kelompok Wirausaha Pemuda (KWP)âs earnings was difference of capital help which was given, fish conducting experience, and fish death rate. average of contribution Earnings of fishery fish conducting business equal to 56%s and of result of revenue analysis by using UMK Kota Palangka Rayaâs standard, number of members of group of KWP which entered categorizing poor and was not poor was proportional or equal namely 15 people or 50 %s. with existence of activity of fish conducting by using pool and also keramba could increase member of earnings group and fulfilled need to lived, and increases family economic resilience of member of KWP.Keywords: Income, The Group of Young Man Entrepreneurs, and Family Economic Resilience